Cancer chemotherapy practice in dogs and cats in University Veterinary Hospital, UPM : a retrospective study from 2013 to 2017 - Tie, Evelyn Yii Yii (2018)
Most of small animal veterinary practices which provide chemotherapy are in Selangor area, and University Veterinary Hospital (UVH) is one of them. Information on chemotherapy practice in UVH, UPM has not been evaluated retrospectively. The objectives of this study were (1) to determine the number and types of cancer in dogs and cats treated with cytotoxic chemotherapy, (2) to determine the drug types, frequency of delivery and reported side effects based on the various cytotoxic drugs delivered and (3) to determine the costs incurred in chemotherapy protocols of various cancers in dogs and cats presented to UVH between 2013 and 2017. The study was conducted retrospectively by reviewing case log books available in the Chemotherapy Room and records in UVH. The data collected was subjected to descriptive analysis using SPSS version 20.0. Fisher’s exact test and Kaplan-Meier analysis were performed where necessary. P-value <0.05 was considered statistically significant at 95% confidence interval. A total of 113 animals received cytotoxic chemotherapy for cancer in UVH (83 dogs and 30 cats). A total of 429 doses (78%) of injectable cytotoxic drugs were delivered to dogs and 123 doses (22%) to cats. The most common cancer treated in dogs was transmissible venereal tumour while lymphoma in cats. Vincristine is the most frequently used injectable cytotoxic anti-cancer chemotherapy drug with a total of 474 doses delivered over the five years. Common side effects of chemotherapy in both dogs and cats were anaemia and thrombocytopenia, with a single case of drug extravasation tissue reaction. The average cost for chemotherapy delivery per visit regardless of species was RM 247. This study revealed that high number of cytotoxic drugs are delivered to dogs compared to cats and nevertheless the safety precautions are necessary for all staff handling and working with cytotoxic chemotherapy.